URGENSI HUKUM WARIS NASIONAL SETELAH BERLAKUNYA UNDANG-UNDANG NO.23 TAHUN 2006 TENTANG ADMINISTRASI KEPENDUDUKAN - Limurti, Dewi Fortuna (Faculty of Law, Parahyangan Catholic University, 2022)
Inheritance Law is the only area of law that still applies different laws for Indonesian citizens with varying groups as regulated in Articles 131 and 163 of the Indische Staats regeling. With the enactment of Law Number 23 Year 2006 concerning Population Administration (UU Adminduk), in Article 106 all Staatsblads regulating the classification of residents in the Birth Certificate are revoked, so that since such Law came into effect, there were no more instructions in the Birth Certificate regarding the classification of an Indonesian citizen. This has had a significant impact on the enforcement of the Inheritance Law, which is still enforce based on the classification of the resident groups. This paper uses a normative juridical approach, so that the urgency of the formation of the National Inheritance Law will be seen from the point of view of legislation, jurisprudence, doctrine and legal literature. Apart from the goal as an independent nation to have a national law, it is also necessary to understand that inheritance law must be formed in accordance with the pluralistic conditions of the Indonesian nation. Raising awareness of the importance of establishing a National Inheritance Law is the aim of this paper, especially as an appreciation of the abolition of population classification by UU Adminduk, and the need for a national law that is in accordance with the spirit of the Indonesian nation, i.e Pancasila.